2023
DOI: 10.3390/ph16121652
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals as Immunomodulatory Molecules in Cancer Therapeutics

Sandeep Paudel,
Neha Mishra,
Rajesh Agarwal

Abstract: Phytochemicals are natural plant-derived products that provide significant nutrition, essential biomolecules, and flavor as part of our diet. They have long been known to confer protection against several diseases via their anti-inflammatory, immune-regulatory, anti-microbial, and several other properties. Deciphering the role of phytochemicals in the prevention, inhibition, and treatment of cancer—unrestrained cell proliferation due to the loss of tight regulation on cell growth and replication—has been the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 202 publications
0
5
0
Order By: Relevance
“…Echinacea purpurea has promising antioxidant capabilities, the majority of which are linked to the high concentrations of bioactive phenolic components (Paudel et al 2023 ; Wojdylo et al 2007 ; Dogan et al 2014 ). However, there are few available findings on the beneficial influences of E. purpurea root extract in mammals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Echinacea purpurea has promising antioxidant capabilities, the majority of which are linked to the high concentrations of bioactive phenolic components (Paudel et al 2023 ; Wojdylo et al 2007 ; Dogan et al 2014 ). However, there are few available findings on the beneficial influences of E. purpurea root extract in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Derivatives of caffeic acid particularly cichoric acid have a wide range of biological properties, inclusive of collagen protection, anti-hyaluronidase activity, antiviral activity, phagocyte activity promotion, and high antioxidant capacity (Barnes et al 2005 ; Bauer and Wagner 1991 ; Pellati et al 2004 ). Furthermore, E. purpurea possesses antifungal, antibacterial, anti-inflammatory, and anti-cancer activities (Paudel et al 2023 ; Kabir et al 2022 ; Hudson 2012 ; Gurley et al 2012 ). Numerous investigations have shown that E. purpurea extracts efficiently protect against liver damage brought on by alcohol, chemical pollutants, and obesity (Xiao et al 2013 ; Smalinskiene et al 2007 ; Landmann et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…They have been used as adjuvant therapies in several conditions including cancer. Phytochemicals such as curcumin, allicin, alliin, and s-allyl cysteine have been shown to increase the ratio of CD4+/CD8+, enhance the production of IFN-γ in splenocyte of fibroblast tumors, and increase IFN-γ, IL-2 levels in breast cancer in Wistar rats ( 28 ). The efficacy of T. chebula is reported primarily due to the presence of phenolic compounds, which exhibit antioxidant and anti-inflammatory properties ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemicals, mostly polyphenols, are multitarget molecules, like metformin, and they affect many age-related signaling pathways. In fact, it is known that several phytochemicals possess immunomodulatory properties [ 181 ]. For instance, there is clear evidence that phytochemicals can improve the efficacy of many cancer therapies based on PD-1/PD-L1 blockade [ 182 , 183 ].…”
Section: The Anti-aging Signaling Suppresses the Expression Of The Pd...mentioning
confidence: 99%